2020
DOI: 10.1051/0004-6361/201935033
|View full text |Cite
|
Sign up to set email alerts
|

Warm and thick corona for a magnetically supported disk in galactic black hole binaries

Abstract: Context. This paper is devoted to self-consistent modeling of the magnetically supported accretion disk with optically thick warm corona based on first principles. In our model, we consider the gas heating by magneto-rotational instability (MRI) dynamo. Aims. Our goal is to show that the proper calculation of the gas heating by magnetic dynamo can build up the warm, optically thick corona above the accretion disk around black hole of stellar mass.Methods. Using vertical model of the disk supported and heated b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…The temperature of the corona from the MCD+NTHCOMP best-fit model is quite low kT e ∼ 1.68−1.78 keV. This is commonly observed in ULXs (Gladstone et al 2009) and can be ascribed to a cool corona, reminiscent of the soft X-ray excess often observed in some BH accreting sources (Gronkiewicz & Różańska 2020;Petrucci et al 2020, and references therein).…”
Section: Spectral Analysismentioning
confidence: 86%
“…The temperature of the corona from the MCD+NTHCOMP best-fit model is quite low kT e ∼ 1.68−1.78 keV. This is commonly observed in ULXs (Gladstone et al 2009) and can be ascribed to a cool corona, reminiscent of the soft X-ray excess often observed in some BH accreting sources (Gronkiewicz & Różańska 2020;Petrucci et al 2020, and references therein).…”
Section: Spectral Analysismentioning
confidence: 86%
“…It also implies that for lower Eddington ratio objects the instability would not operate, while for higher Eddington ratio objects this mechanism would lead to outbursts of a much larger part of the disk and it would operate on a timescale of thousands of years, as typically predicted for the radiation pressure instability (Janiuk et al 2002;Czerny et al 2009;Wu et al 2016;Grze ¸dzielski et al 2017). However, if the evolution includes the time-dependent coronal flow (e.g., Janiuk & Czerny 2007) or time-dependent vertical stratification of the disk into cold standard disk and the warm corona (e.g., Czerny et al 2003b;Gronkiewicz & Różańska 2020;Petrucci et al 2020), the timescales will be strongly affected by quadratic dependence of the viscous timescale on the ratio of the local medium geometrical thickness to the local radius.…”
Section: Discussionmentioning
confidence: 96%
“…However, through recent radiative transfer computation in hydrostatic and radiative equilibrium, Gronkiewicz & Różańska (2020) has shown that for lower accretion rates, thermal instability should prevent the warm corona from forming. The low accretion rate system is unable to provide enough energy to sustain a warm corona (Ballantyne & Xiang 2020).…”
Section: Physical Properties Of the Warm Corona Modelmentioning
confidence: 99%